2023
DOI: 10.3390/nu15214643
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Eating Disorders and Disordered Eating Behaviours amongst Adolescents and Young Adults in Saudi Arabia: A Systematic Review

Azzah Alsheweir,
Elizabeth Goyder,
Ghadah Alnooh
et al.

Abstract: Eating disorders (EDs) and disordered eating behaviours (DEBs) are significant health problems related to body image and weight dissatisfaction among adolescents and young adults worldwide. During this stage of sensitive development, these behaviours may hinder the optimal growth process and can consequently lead to wasting, stunting, and micronutrient deficiencies. However, there is a limited amount of literature on DEB among Arab populations, particularly in Saudi Arabia. This review aims to assess the preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 110 publications
2
3
0
Order By: Relevance
“…This was consistent with earlier and recent findings that confirmed that the prevalence and intensity of DEB increased with age [2,[25][26][27][28]49]. It was also compatible with our systematic review findings that identified an elevated risk of DEB among older Saudi students compared with younger counterparts [29]. A rationale for this distinct pattern is the age-related increase in self-consciousness, including interior and exterior aspects of self, associated with concerns of social acceptance and selfpresentation [50].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This was consistent with earlier and recent findings that confirmed that the prevalence and intensity of DEB increased with age [2,[25][26][27][28]49]. It was also compatible with our systematic review findings that identified an elevated risk of DEB among older Saudi students compared with younger counterparts [29]. A rationale for this distinct pattern is the age-related increase in self-consciousness, including interior and exterior aspects of self, associated with concerns of social acceptance and selfpresentation [50].…”
Section: Discussionsupporting
confidence: 92%
“…A meta-analysis assessed the level of DEB in children and adolescents aged 7 to 18 years from 16 different countries, including Saudi Arabia, and found that more practices of disordered eating were reported with increasing age [ 28 ]. The findings from our systematic review, focusing specifically on Saudi Arabia, were also consistent with the age pattern and DEB, as it was noted that older university students had more DEBs (29.4–65.5%) compared with school students (10.2–42.5%) [ 29 ].…”
Section: Introductionsupporting
confidence: 81%
See 3 more Smart Citations